Λησμονημένα ίχνη. Η παρέμβαση του Δημήτρη Μορτόγια (1934-1975) - Κατσαβέλη, Ελένη; Μικέ, Μαίρη (Σύγκριση/Comparaison/Comparison, 2023)
Mairi Mike Eleni Katsaveli Forgotten traces The intervention of Dimitris Mortogias (1934-1975) Retracing Mortogia's forgotten impact on the public sphere and rediscovering his identity as a writer become set goals for this joint research. Ranging from poetry to critical aspects and then to translations Mortogia's work is placed in its ideological and aesthetic contextual background. After the study of the primary material, the main impetus for research on this topic is to extract the way in which issues and aesthetic criteria were examined in this period and to analyze the new issues that were formed, in order to show what has changed, modified, maintained or overturned. His mark on the post-Junta movements is examined through a genealogical lense – sheding light on the innovating character of his critical views. In the Appendix I of the essay, Mortogia’s ergography is composed for first time and in Appendix II, un unpublished text about the dictatorship in Greece comes to light. Λέξεις κλειδιά: Dimitris Mortogias, critical issues 20th century, post-Junta reception